2019
DOI: 10.1523/jneurosci.0882-19.2019
|View full text |Cite|
|
Sign up to set email alerts
|

Promiscuous G-Protein-Coupled Receptor Inhibition of Transient Receptor Potential Melastatin 3 Ion Channels by Gβγ Subunits

Abstract: Transient receptor potential melastatin 3 (TRPM3) is a nonselective cation channel that is inhibited by G␤␥ subunits liberated following activation of G␣ i/o protein-coupled receptors. Here, we demonstrate that TRPM3 channels are also inhibited by G␤␥ released from G␣ s and G␣ q. Activation of the G s-coupled adenosine 2B receptor and the G q-coupled muscarinic acetylcholine M1 receptor inhibited the activity of TRPM3 heterologously expressed in HEK293 cells. This inhibition was prevented when the G␤␥ sink ␤AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 33 publications
0
39
2
Order By: Relevance
“…Instead, these data raise the possibility that increased molecular and functional expression of TRPM3 in neurons innervating inflamed tissue increases the excitability of nociceptors co-expressing TRPA1 and TRPV1, contributing to the augmented responses to agonist stimulation. This interpretation also provides a straightforward mechanism for the observation that heat hyperalgesia does not develop in TRPM3-deficient mice and is fully alleviated by TRPM3 antagonists (14,16). Since heat hyperalgesia is also strongly attenuated by pharmacological inhibition or genetic ablation of TRPV1 (10-13), we hypothesize that those DRG neurons that gain functional coexpression of TRPM3 and TRPV1 under inflammatory conditions play a central role in the development of heat hypersensitivity.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Instead, these data raise the possibility that increased molecular and functional expression of TRPM3 in neurons innervating inflamed tissue increases the excitability of nociceptors co-expressing TRPA1 and TRPV1, contributing to the augmented responses to agonist stimulation. This interpretation also provides a straightforward mechanism for the observation that heat hyperalgesia does not develop in TRPM3-deficient mice and is fully alleviated by TRPM3 antagonists (14,16). Since heat hyperalgesia is also strongly attenuated by pharmacological inhibition or genetic ablation of TRPV1 (10-13), we hypothesize that those DRG neurons that gain functional coexpression of TRPM3 and TRPV1 under inflammatory conditions play a central role in the development of heat hypersensitivity.…”
Section: Discussionmentioning
confidence: 84%
“…In recent work, we demonstrated that three TRP channels (TRPM3, TRPV1 and TRPA1) act as redundant sensors of acute heat: neuronal heat responses and heat-induced pain are preserved in mice in which two of these three TRP channels were genetically ablated, but combined elimination of all three channels fully abolishes the withdrawal reflex from a noxious heat stimulus (9). Notably, earlier work had also revealed an absolute requirement of both TRPV1 and TRPM3 for the development of inflammatory heat hypersensitivity, since genetic ablation or pharmacological inhibition of either channel individually fully abrogates heat hyperalgesia in the rodent CFA model (10)(11)(12)(13)(14)(15)(16). These combined findings suggested that inflammation modulates the functional interplay between these heat-activated TRP channels leading to pathological heat hypersensitivity, but the underlying processes and mechanisms remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of heat-sensing domains, it is notable that PS-activation of a truncated hTRPM3 channel (hTRPM3 1325 ) was not enhanced by heat [68] raising the possibility that C-terminal sequences may be involved in heat sensitivity. Other cytoplasmic sequences including those at the C-terminus may also serve as interaction sites for TRPM3 channel inhibition by Gβγ sub-units [76][77][78][79].…”
Section: Trpm3 and Ocular Ca 2+ Dynamicsmentioning
confidence: 99%
“…In vitro functional expression studies have determined that TRPM3 channels are activated by several structurally unrelated agonists including (1) the endogenous excitatory neurosteroid pregnenolone sulfate, which can also weakly activate TRPM1 channels [51,[57][58][59][60][61][62][63]; (2) cell-membrane phosphoinositol phosphates [64][65][66]; and (3) noxious heat [46][47][48][49][50]. Conversely, they are inhibited by (1) certain clinically approved drugs including nonsteroidal anti-inflammatory drugs (NSAIDs, e.g., mefenamic acid), antibiotics (e.g., voriconazole, which also inhibits TRPM1 channels), sex-steroids (e.g., progesterone), and synthetic drug-like antagonists [40,41,51,61,[67][68][69][70][71][72]; (2) naturally occurring plant-derived secondary metabolites (e.g., citrus flavanones) [73][74][75]; and (3) Gprotein coupled receptor βγ subunits [76][77][78][79]. By contrast, TRPM1 channels were found to be inhibited by interaction with both Gα or Gβγ subunits [80].…”
Section: Introductionmentioning
confidence: 99%